Laser interstitial thermal therapy (LITT) for pediatric patients affected by intracranial tumors - Spacca, Barbara; Di Maurizio, Marco; Grandoni, Manuela; Tempesti, Sara; Genitori, Lorenzo (Frontiers in Neurology, 2023)
Introduction: Surgical treatment of brain tumor evolved over time offering different strategies tailored on patients and lesions. Among them, LITT is one of the most recent in pediatric neurooncological surgery and its results and evolution are still under assessment. Materials and Methods: We retrospectively analyzed data of six pediatric patients with deep seated brain tumors treated with LITT in a single center between November 2019 and June 2022. Four patients underwent, in the same operating session, to a stereotaxic biopsy. Indication and preparation to LITT, technical issues, clinical and radiological follow up, impact on quality of life and on oncological treatment are discussed. Results: Mean age was 8 years (range 2 years - 11 years). The lesion was thalamic in four patients, thalamo-peduncular in one, occipital posterior periventricular in one. Two patients had a low-grade glioma (LGG) previously diagnosed. Biopsies resulted in LGG in two patients, ganglioglioma grade I in one, and diffuse high-grade glioma (HGG) in one. Postoperatively, two patients presented a transient motor deficit. Mean follow up was 17 months (range 5 months – 32 months). The radiological follow up showed a progressive reduction of the tumor in patients with LGG. Conclusions: LITT is a promising minimally invasive treatment for deep seated tumors in children. The results in terms of lesion reduction appear relevant in low-grade gliomas and continue over time. It can be used as an alternative treatment for tumors located in sites that are difficult to access surgically or where other standard treatment options have failed.